2021
DOI: 10.1101/2021.05.28.21258000
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insulinopathies of the brain? Genetic overlap between somatic insulin-related and neuropsychiatric disorders

Abstract: The prevalence of Alzheimer's disease (AD), autism spectrum disorder (ASD), and obsessive-compulsive disorder (OCD) is higher among patients with somatic insulinopathies, like metabolic syndrome (MetS), obesity, and type 2 diabetes mellitus (T2DM). Dysregulation of insulin signalling has been implicated in these neuropsychiatric disorders, and shared genetic factors might partly underlie these observed comorbidities. We investigated genetic overlap between AD, ASD, and OCD with MetS, obesity, and T2DM by estim… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…This may suggest that shared risk factors are at play. Indeed, recent data-driven genome-wide approaches indicate that T2DM and most of the psychiatric disorders share genetic risk factors [42]. Still, for several of the disorders, estimated effects were of different size in the two temporally ordered analyses, which could be explained by specific disease-related risk factors influencing the association in the one direction.…”
Section: Temporal Order Of T2dm and Brain Disordersmentioning
confidence: 98%
See 1 more Smart Citation
“…This may suggest that shared risk factors are at play. Indeed, recent data-driven genome-wide approaches indicate that T2DM and most of the psychiatric disorders share genetic risk factors [42]. Still, for several of the disorders, estimated effects were of different size in the two temporally ordered analyses, which could be explained by specific disease-related risk factors influencing the association in the one direction.…”
Section: Temporal Order Of T2dm and Brain Disordersmentioning
confidence: 98%
“…Studies have also found associations between T2DM and disorders of the brain, including vascular dementia and Alzheimer's disease [10], substance use disorder, schizophrenia, bipolar disorder, depression, personality disorder, and attention-deficit/ hyperactivity disorder (ADHD) [11][12][13][14][15][16][17], obsessive-compulsive disorder (OCD) [18], cognitive impairment [19], and also of filling a prescription for psychotropic drugs, including antidepressants, antipsychotics, and anxiolytics [20]. Recently, the term "insulinopathies of the brain" has been suggested to characterize these associations between T2DM and brain disorders [21,22]. It should be noted that from here and onwards we use the term brain disorder when referring to a broad range of specific psychiatric and neurological disorders, although late-onset neurodegenerative disorders were not assessed in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…Type 2 diabetes mellitus (T2DM) is a metabolic disease with an increasing incidence worldwide (Lees et al, 2009;Bobbert et al, 2013). This disease constitutes a risk factor associated with an increased incidence of cognitive dysfunctions and emotional disorders [e.g., Parkinson's disease (PD), Alzheimer's disease (AD), obsessive-compulsive disorder (OCD), and major depressive disorder (MDD)] (den Braber et al, 2010;Pan et al, 2010;Zhang et al, 2013;Ashraghi et al, 2016;Athauda and Foltynie, 2016;De Pablo-Fernandez et al, 2018;Cheong et al, 2020;Wei et al, 2020;Sánchez-Gómez et al, 2021;Fanelli et al, 2022). However, the specific neural substrate of T2DM-related cognitive impairment and emotional disorders remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic correlation was relatively moderate between schizophrenia and attention deficit/ hyperactivity disorder (ADHD) [13]. Stratified analyses showed negative genetic covariances between schizophrenia and somatic insulinopathies through gene sets related to insulin signaling and insulin receptor recycling [14]. Strongest associations were confirmed between type 2 diabetes mellitus and schizophrenia spectrum disorder [15].…”
Section: Introductionmentioning
confidence: 99%